2019
DOI: 10.1111/jspn.12239
|View full text |Cite
|
Sign up to set email alerts
|

First bathing time of newborn infants after birth: A comparative analysis

Abstract: Purpose: The study was designed as an experimental study to describe the effect of the first bathing time on the body temperature and skin moisture of a newborn after birth.Design and Methods: The study population consisted of term newborns between JanuaryThe sample group was randomly divided into two groups according to different bathing times. The first group (39 infants) was given a bath 24 hr after birth, and the second group (34 infants) was given a bath 48 hr after birth. The infants in both the groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
0
11
0
8
Order By: Relevance
“…Therefore, bathing in the early neonatal period is thought to cause heat loss in late preterm infants. Gözen et al (2019) found that delaying the first bathing until 48 hr after birth was effective in maintaining the body temperature and increasing the skin moisture of 73 term infants.…”
Section: Development Of the Skin's Barrier Function Is Reflected By Bmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, bathing in the early neonatal period is thought to cause heat loss in late preterm infants. Gözen et al (2019) found that delaying the first bathing until 48 hr after birth was effective in maintaining the body temperature and increasing the skin moisture of 73 term infants.…”
Section: Development Of the Skin's Barrier Function Is Reflected By Bmentioning
confidence: 99%
“…Inclusion and exclusion criteria were established in accordance with the literature (Gözen et al, 2019;Taşdemir & Efe, 2019).…”
Section: Recruitment Will Continue Until 76 Participants Have Met Thementioning
confidence: 99%
See 3 more Smart Citations